Can C7 Slope Be Used as a Substitute for T1 Slope? A Radiographic Analysis. Issue 2 (April 2020) - Ye, Ivan B.; Tang, Ray; Cheung, Zoe B.; White, Samuel J. W.; Cho, Samuel K.
Study Design: Retrospective radiographic study. Objectives: T1 slope is an important parameter of sagittal spinal balance. However, the T1 superior endplate can be difficult to visualize on radiographs due to overlying anatomical structures. C7 slope has been proposed as a potential substitute for T1 slope when the T1 superior endplate is not well visualized. The objective of this study was 2-fold: (1) to assess the correlation between C7 and T1 slopes on upright cervical spine radiographs and (2) to evaluate the interrater reliability of C7 slope. Methods: Cervical spine radiographs taken between December 2017 and June 2018 at a single institution were reviewed. Two observers measured upper C7 slope, lower C7 slope, and T1 slope. The correlations between upper and lower C7 slope and T1 slope were evaluated, and linear regression analyses were performed. Interrater reliability of C7 slope was also assessed. Results: In this cohort of 152 patients, there was a strong correlation between upper C7 slope and T1 slope ( r = 0.91, P < .001), as well as between lower C7 slope and T1 slope ( r = 0.90, P < .001). T1 slope could be estimated from the linear regression equation, T1 slope = 0.87 × C7 slope + 7, with an overall model fit of R 2 = 0.8. There was strong interrater reliability for upper (intraclass correlation coefficient [ICC] = 0.95, P < .001) and lower C7 slope (ICC = 0.96, P < .001). Conclusions: Both the upper and lower C7 slope are strongly correlated with T1 slope and can be used as a substitute to estimate T1 slope when the superior endplate of T1 is not well visualized.